Lições de descolonização: sujeito e memória, emancipação e transdisciplinaridade numa palestra-performance de Grada Kilomba - Rosa, Sophia Toledo (2021)
Grada Kilomba is an artist and academic who in recent years has been dedicating herself to performances, films and installations through a transdisciplinary approach to address diverse themes involving racism in the post-colonial world. This research will deal with the lecture-performance called Decolonizing knowledge held in 2016 at Centro Cultural São Paulo. The objective is to analyze how the artist deconstructs the dominant discourse inherited from colonialism by breaking traditional forms of representation of the academic discourse, understanding how she builds the discourse of decolonization of knowledge through transdisciplinarity. To this end, we present concepts who are in the performance as reflections on the concept of transdisciplinarity and the different perspectives and studies regarding decolonization. Next, we make a biographical synthesis and the trajectory of Grada Kilomba, exposing one of her milestones in literary production: the book Memórias da Plantação (2008) which is addressed in the lecture-performance Decolonizing knowledge that we will analyze from the division proposed by the artist herself who uses different languages to demonstrate that it is necessary not to forget that production of knowledge is always located in a place and in a history, therefore, it cannot be neutral and universal